2018
DOI: 10.1002/hbm.24344
|View full text |Cite
|
Sign up to set email alerts
|

The system‐neurophysiological basis for how methylphenidate modulates perceptual–attentional conflicts during auditory processing

Abstract: The ability to selectively perceive and flexibly attend to relevant sensory signals in the environment is essential for action control. Whereas neuromodulation of sensory or attentional processing is often investigated, neuromodulation of interactive effects between perception and attention, that is, high attentional control demand when the relevant sensory information is perceptually less salient than the irrelevant one, is not well understood. To fill this gap, this pharmacological-electroencephalogram (EEG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 95 publications
(218 reference statements)
3
16
1
Order By: Relevance
“…Previous data has already suggested that BA7 and BA39 are involved in inhibitory control when these processes are modulated by perceptual conflicts (Bodmer & Beste, 2017). Parietal areas seem to be involved in cognitive control whenever sensory information is complex or conflicting yet essential for behavioral control (Adelhöfer et al, 2018;Fokin et al, 2008;Ocklenburg et al, 2011;Takeichi et al, 2010). This notion fits in well with findings showing that BA40 and BA7 bridge perception and action (Gottlieb, 2007) and that elevated demands on conflict monitoring involve the superior and inferior parietal cortices (Gothelf et al, 2007).…”
Section: Resting Theta Activity Groupingsupporting
confidence: 78%
See 3 more Smart Citations
“…Previous data has already suggested that BA7 and BA39 are involved in inhibitory control when these processes are modulated by perceptual conflicts (Bodmer & Beste, 2017). Parietal areas seem to be involved in cognitive control whenever sensory information is complex or conflicting yet essential for behavioral control (Adelhöfer et al, 2018;Fokin et al, 2008;Ocklenburg et al, 2011;Takeichi et al, 2010). This notion fits in well with findings showing that BA40 and BA7 bridge perception and action (Gottlieb, 2007) and that elevated demands on conflict monitoring involve the superior and inferior parietal cortices (Gothelf et al, 2007).…”
Section: Resting Theta Activity Groupingsupporting
confidence: 78%
“…Processes related to the conflict monitoring modulate theta activity (Cohen & Donner, 2013;Lavallee et al, 2014;Tang et al, 2013;Wang et al, 2014). Parietal areas seem to be involved in cognitive control whenever sensory information is complex or conflicting yet essential for behavioral control (Adelhöfer et al, 2018;Fokin et al, 2008;Ocklenburg et al, 2011;Takeichi et al, 2010). Importantly, however, the current data show that the strength of resting theta band power plays a decisive role in the modulation of cognitive control-related total theta band activity, especially during conflict-modulated response inhibition.…”
Section: Resting Theta Activity Groupingcontrasting
confidence: 56%
See 2 more Smart Citations
“…The P3 ERP-component seems to be sensitive only to rule-based differences and not to statistical properties (Kóbor et al, 2018). In the EEG, the N2 is not a unitary component: it can be divided into different subcomponents related to cognitive control and stimulus-related detection of novelty information processing (Adelhöfer et al, 2018(Adelhöfer et al, , 2019Chmielewski et al, 2018;Folstein and Van Petten, 2008b;Mückschel et al, 2017a). Specifically, subprocesses in the N2 time window that are affected by stimulus-related information can be expected to show sensitivity to statistical learning.…”
Section: Introductionmentioning
confidence: 99%